German translation and validation of the reporting of clinical adverse events scale (RoCAES-D) - Litke, Nicola; Wensing, Michel; Miksch, Antje; Krug, Katja (BMC health services research, 2020)
Reporting of adverse events is an important aspect of patient safety management in hospitals, which may help to prevent future adverse events. Yet, only a small proportion of such events is actually reported in German hospitals. Therefore, it is crucial to evaluate attitudes of clinical staff towards reporting of adverse events. The aim of this study was to translate the Reporting of Clinical Adverse Events Scale (RoCAES) developed by Wilson, Bekker and Fylan (2008) and validate it in a sample of German-speaking health professionals. The questionnaire covers five factors (perceived blame, perceived criteria for identifying events that should be reported, perceptions of colleagues’ expectations, perceived benefits of reporting, and perceived clarity of reporting procedures) and was translated into German language according to translation guidelines. Within a cross-sectional study in a sample of 120 health professionals in German hospitals, internal consistency (omega) and construct validity (confirmatory factor analysis) of the German scale RoCAES-D was assessed. The reliability was high (omega = 0.87) and the factor analysis showed a poor model fit (RMSEA: 0.074, χ2/df: 1.663, TLI: 0.690). Resulting from lower model fit of the original model (RMSEA: 0.082, χ2/df: 1.804, TLI: 0.606), one item was deleted due to low factor loadings and a low R2 (0.001), and two items were reallocated from the factor ‘perceived benefits’ to ‘perceived blame’. The successful translation and initial validation of the RoCAES-D might be a good starting point for further research. A cultural adaptation of the scale needs to be done to initiate a large-scale usage of the questionnaire.
Gesehen am 11.09.2020